2005
DOI: 10.1128/jvi.79.3.1934-1942.2005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Interferon Signaling by the New York 99 Strain and Kunjin Subtype of West Nile Virus Involves Blockage of STAT1 and STAT2 Activation by Nonstructural Proteins

Abstract: The interferon (IFN) response is the first line of defense against viral infections, and the majority of viruses have developed different strategies to counteract IFN responses in order to ensure their survival in an infected host. In this study, the abilities to inhibit IFN signaling of two closely related West Nile viruses, the New York 99 strain (NY99) and Kunjin virus (KUN), strain MRM61C, were analyzed using reporter plasmid assays, as well as immunofluorescence and Western blot analyses. We have demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
246
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(262 citation statements)
references
References 31 publications
11
246
3
Order By: Relevance
“…Previously, it was shown that a single JEV E protein mutation (E138K) increased virus sensitivity to type I IFN, but this phenotype was coupled with altered levels of virus replication in tissue culture, 60 unlike the E protein mutations in JEV SA14-14-2 variants 2 IFN and C. However, the JEV NS4A protein and the NS2B and NS3 proteins of genetically related West Nile virus Kunjin are known to function as type I IFN-antagonists. 61,62 Therefore, it is likely that one or more unique non-structural protein mutations in JEV SA14-14-2 variants C, 2 IFN and 5 IFN modulated sensitivity to type I IFN in Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was shown that a single JEV E protein mutation (E138K) increased virus sensitivity to type I IFN, but this phenotype was coupled with altered levels of virus replication in tissue culture, 60 unlike the E protein mutations in JEV SA14-14-2 variants 2 IFN and C. However, the JEV NS4A protein and the NS2B and NS3 proteins of genetically related West Nile virus Kunjin are known to function as type I IFN-antagonists. 61,62 Therefore, it is likely that one or more unique non-structural protein mutations in JEV SA14-14-2 variants C, 2 IFN and 5 IFN modulated sensitivity to type I IFN in Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…The anamnestic response among YF-immune subjects could have great implications for the development of an immunization strategy for a tetravalent vaccine by avoiding the potential interference problem that presenting a single YF-DEN chimeric virus poses to the host. In this instance, the induction of interferon occurs in concert with virus replication and is modulated effectively by the YF nonstructural proteins 18,19 to allow sufficient replication required for immunization. Since the initial immunizing agent (YF) is incapable of sensitizing the subject to DHF, there will be no danger that the first (priming) inoculation would leave the subject vulnerable to this disease if the second injection was delayed or not administered.…”
Section: Discussionmentioning
confidence: 99%
“…However, use of IFN-␣/␤ in clinical trials for treatment of flavivirus infection has not been uniformly successful (34,50). This may be explained by the ability of some flaviviruses, including dengue virus serotype 2 (DEN-2), Japanese encephalitis virus, West Nile virus (WNV), and Kunjin virus (KUN) (16,30,33,38,39), to inhibit the JAK-STAT (Janus kinasesignal transducer and activator of transcription) pathway in response to IFN-␣/␤ and/or IFN-␥. Efforts to determine the specific gene products of these viruses responsible for IFN antagonism have implicated the nonstructural proteins.…”
mentioning
confidence: 99%